Ground-Dwelling arachnids and fire disturbance: A case study in Northeastern Patagonia (Argentina) - Martínez, Fernando Joaquín (2022)
Fire is one of the main disturbances in northeastern Patagonia. Wildfires are becoming more frequent and severe, threatening the sustainability of local ecosystems. Arachnids respond markedly to environmental modifications and can regulate processes linked to lower trophic levels. Assessing changes in arachnid diversity is useful to understand the effect of fire on animal assemblages and ecosystem functionality. The aim of this study was to analyze the response of the ground-dwelling arachnid assemblage to fire disturbance. Eight sampling sites were selected: four burned and four unburned. Arachnids were sampled using pitfall traps. The taxonomic and functional structure of the assemblage was found to differ between burned and unburned areas. This change was related to major taxa turnover. On the other hand, the alpha diversity did not differ significantly according to fire disturbance. The abundance of specialist spiders decreased significantly in burned areas, possibly related to post-fire changes in the composition and structure of the plant community. In addition, significant species indicators of unburned and burned sites were found. The results of this study are useful for ecosystem management and the development of biodiversity conservation strategies in northeastern Patagonia, an area severely affected by fires.